Natural bioactive compounds form herbal medicine in Alzheimer’s disease: from the perspective of GSK-3β - Wang, Mei; Huang, Wendi; Huang, Juan; Luo, Yong; Huang, Nanqu (Frontiers in Pharmacology, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline and memory loss. Glycogen synthase kinase 3β (GSK-3β) plays a pivotal role in AD pathogenesis, particularly in tau protein hyperphosphorylation. Natural bioactive compounds have a wide range of sources, and medicinally valuable active compound can be extracted from plants, animals, and microorganisms. Currently, studies have found that various natural bioactive compounds from plants have the potential to improve AD symptoms, such as resveratrol and berberine. Therefore, this review examines the potential of natural bioactive compounds to modulate GSK-3β activity and inhibit the hyperphosphorylation of tau, offering a promising therapeutic strategy for AD. We summarize the current understanding of alkaloids, phenols, flavonoids, terpenoids and other natural compounds, highlighting their mechanisms of action and preclinical efficacy.